Exercise and cognitive function - McMorris, T.; Tomporowski, P.; Audiffren, M. (Wiley-Blackwell, 2009)
This textbook focuses on the relationship between physical exercise and cognition, a very timely and important topic with major theoretical and practical implications for a number of areas including ageing, neurorehabilitation, depression and dementia. It brings together a wide range of analytical approaches and experimental results to provide a very useful overview and synthesis of this growing field of study.